Thor's serpents - Armstrong, Kelley; Marr, Melissa (Armstrong, Kelley. Blackwell pages, 2015)
"As Ragnarok--the apocalypse--approaches, the thirteen-year-old descendants of the gods realize they can't take every step of their journey together, as Matt must fight the Midgard Serpent alone, and Fen and Laurie are pulled in different directions"--